Effect of intake Selenium supplementation on lipid profile and cardiorespiratory function in rest situation and subsequent an exercise session in active men - Khaled Salehi; Fatah Moradi (مجله دانشگاه علوم پزشکی بیرجند, 2019)
Background and Aim: Selenium is an essential mineral with antioxidant properties that play a role in metabolic processes, and its relationship with lipid profile has been shown in some studies. The purpose of this study was to investigate the effect of intake selenium supplementation on lipid profile and cardio-respiratory function in rest situation and subsequent an exercise session in active men. Materials and Methods: The research method was quasi-experimental. In this study, 19 active men were selected from among soccer players in the city of Saghez and were randomly divided into two experimental (supplementation, n=10) and control (placebo, n=9) groups. The assessments were carried out in three stages (pre-taking the supplementation, after taking the supplementation, and immediately after an exercise session).  General characteristics of subjects studied, cardio-respiratory function (aerobic power), and levels of lipid profile (triglyceride (TG), total cholesterol (TC), high-density lipoprotein (HDL), and low-density lipoprotein (LDL)) were measured. Consumption period of supplement was a month. (A 200 μg Selenium capsule per day). To analyze the data, one-factor analysis of variance with repeated measurements was used at a significant level of P<0.05. Results: Selenium supplementation increased cardio-respiratory function (47.7±7.4 vs. 39.7±8.0 ml/kg/min, P=0.017), while has no effect on resting and following exercise session levels of TG (P = 0.258), TC (P=0.737), HDL (P=0.406), and LDL (P=0.312). Conclusion: Taking the selenium supplementation for one month does not seem to affect the components of the on lipid profile in rest situation and subsequent an exercise session, however, it can help improve the cardio-respiratory function of active men.